Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Sepeda Motor Honda Beat : Pada Dealer Raja Jaya Motor Maumere - Krisantus Indratius Roga; Antonius P. Kurniawan; Nunsio H. Meylano (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This study aimed to (1) determine of the effect of quality on purchasing decisions for Honda Beat motorbikes at Raja Jaya Motor Maumere dealers, (2) determine the effect of price on purchasing decisions for Honda Beat Motorbikes at Raja Jaya Motor Maumere dealers, (3) determine the effect of product quality and price on purchasing decisions for Honda Beat motorbikes at Raja Jaya Motor Maumere dealers. In this study, the research design used descriptive and associative methods through a quantitative approach. In this study. The sample size taken using the Slovin formula amounted to 100 respondents who came from consumers of Raja Jaya Motor Maumere dealers. The data was collected through the questionnaire and analyzed using inferential statistics, namely multiple linear regression. Hypothesis testing is done through the T-test and F-test.The results of this study indicated that : (1) partially, the product quality variable had a significant effect on the purchasing decision variable (Y) with a count value of 3.198 > 1.98, (2) partially, the price variable had a significant effect on the purchasing decision variable (Y) with a calculated value of 4.045 > 1.95, (3) together, the two independent variables, namely the product quality variable (X1) and price (X2), had a significant effect on purchasing decisions (Y) with an F-value of 50.611 > 3.09.